Crystal growth experiments in the systems Ni2MSbO6 (M = Sc, In) using chemical vapour transport reactions: Ni2InSbO6 and NiSb2O6 crystals in the millimetre range. Issue 2 (23rd December 2013) - Weil, M.; Mathieu, R.; Nordblad, P.; Ivanov, S. A.
<x xml:space="preserve">Abstract</x> Endothermic chemical vapour transport reactions of polycrystalline Ni2MSbO6 (M = Sc, In) resulted in growth of Ni2InSbO6 and NiSb2O6 crystals in the millimetre range. Their crystal structures were refined from single crystal X‐ray data. Magnetic measurements of Ni2InSbO6 reveal an antiferromagnetic transition near TN = 74 K, accompanied with significant magnetic frustration. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>